Human lymph node microvascular imaging using a fast contrast-free super-resolution ultrasound technique - Amin Naji, Mostafa; Panduro, Nathalie Sarup; Tabatabaei Majd, Seyed Mohammad Mahdi; Hansen, Lauge Naur; Taghavi, Iman; McDermott, Amy; Gundlach, Carsten; Tomov, Borislav Gueorguiev; Nielsen, Michael Bachmann; Sørensen, Charlotte Mehlin; Jensen, Jørgen Arendt (Scientific reports, 2025)
Lymph nodes play a crucial role in cancer metastasis, and assessing lymph node involvement is essential for patient prognosis and treatment strategies. Super-resolution ultrasound imaging (SRUS), including ultrasound localization microscopy (ULM), has shown promise in visualizing the lymph node microvasculature, however, ULM requires microbubbles injection, monitoring, and long acquisition times. This study investigates the feasibility of using a fast contrast-free SRUS approach based on erythrocytes (SURE) to visualize and quantify the microvasculature in human lymph nodes. The SURE pipeline detects and tracks erythrocyte scatterer peaks to generate high-resolution microvascular images with a resolution of less than half the wavelength in 2 seconds of data acquisition. SURE visualized the microvasculature, flow direction, and velocity in four normal human lymph nodes, detecting vessels as small as 40 m in diameter and blood flow velocities ranging from 2 to 15 mm/s. The time evolution of SURE images from 0.1 to 10 seconds was demonstrated, and the SURE consistency was validated by processing SURE images of the same lymph node acquired at different time points. The SURE approach offers a fast contrast-free method for assessing human lymph node microvascular characteristics, providing a promising tool for lymph node evaluation in clinical settings.